PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR PEWARNAAN DOUBLE APLIKASI - Fatmasari, Fitria Hansyah; Susilowati, Susilowati (Steam Engineering, 2025)
Hybrid learning at SMK Negeri 2 Jombang greatly affects students' understanding of the learning outcomes of double application coloring (tipping). This study aims to analyze the effect of the implementation of a scientific approach that affects the learning outcomes of double application coloring (Tipping) of grade 11 students of SMK Negeri 2 Jombang. The research method used is an experiment with a pretest-posttest control group design. The sample used in this study was class 11 Beauty of SMK N 2 Jombang. The results of the study showed that there was an influence of a scientific approach on the learning outcomes of double application coloring (tipping) on ​​students' cognitive learning outcomes as evidenced by the results of the t-test sig value of 0.000 which was smaller than the real price of 0.05 or 0.000> 0.05. In addition, there was a difference in the average posttest results in the control class of 66.50 and the experimental class of 81.96